Efforts to Increase Consumer Buying Interest and Satisfaction through the Influence of Price and Product Perception on the Social Safety Net West Nusa Tenggara Gemilang - Zulkieflimansyah; Santoso, Agus; Hartini; Maradita, Fendy; Nurjihadi, Muhammad (HM Publisher, 2022)
The social safety net (JPS) is one of the eight flagship programs of West Nusa Tenggara (NTB) Gemilang. JPS is an aid provided by the government in the form of a package containing nine staples for communities affected by the pandemic. This research aims to test the influence of price and product perception on consumer buying interest and consumer satisfaction in the people who receive the help of JPS NTB Gemilang. NTB people who received this program package became a population in this study, with 100 respondents taken from each province in NTB using questionnaires and data analysis using the structural equation model. The results showed that price perception affects consumer buying interest, products affect consumer buying interest, price perception affects consumer satisfaction, products affect consumer satisfaction. This research resulted in the perception of prices by the community and local products used in the program can increase people's buying interest in products in the program and provide satisfaction felt by the community after receiving packages in the JPS NTB Gemilang program.